Osseous surgery: Traditional vs fiber retention resective surgery - Mohamed M. Meghil; Celine J. Cornelius Timothius; Elizabeth C. Miller; Mira Ghaly (Elsevier, 2022)
Periodontitis is a disease originating from bacteria in a susceptible host, in which a nonprotective, chronic inflammatory process results in the destruction of supporting soft and hard tissues surrounding the teeth, eventually causing the loss of dentition over time. The ultimate goal of periodontal treatment is to control the progression of periodontal disease. This is achieved by removing the causative factors and stopping progression of clinical attachment loss and ultimately preventing loss of teeth. Osseous resective surgery (ORS) is one of the treatment modalities used to gain access to the root surfaces and boney defects, visualize removal of plaque and calculus from the root surfaces, and reestablish proper bone and soft tissue contours in order to facilitate removal of plaque by the patient as well as dental professionals. Osseous resective surgery fiber retention (FibReORS) is another less commonly used variation of this resective approach. Although it has shown promising results, little research exists comparing the two approaches. The aim of this review is to revisit the dogma of traditional ORS and highlight the differences between the two surgical approaches in regard to clinical procedures, clinical outcomes, and patient's reported outcomes.